A Case for Using the Psychodynamic Diagnostic Manual-2 Instead of the Diagnostic and Statistical Manual of Mental Disorders-5 in University and College Counseling Centers. Issue 1 (2nd January 2022) - Polychronis, Paul D.; Keyes, Lee N.
ABSTRACT: Counseling centers are part of a national practice environment that arguably encourages expedience rather than thoroughness in working with psychological difficulties. In this landscape, diagnosis is a process where symptom identification is preferred over a more complex understanding of clients. The predominant diagnostic tool used by mental health professionals is the Diagnostic and Statistical Manual of Mental Disorders (DSM) which has the main purpose of identifying symptom clusters. A less known competitor to the DSM is the Psychodynamic Diagnostic Manual (PDM). Purposefully developed as an alternative to the DSM, the PDM has many unique features and differences that distinguish it from the DSM. Compared to the DSM, the PDM requires a more labor-intensive and thorough assessment process. That process assists clinicians in arriving at a multifaceted diagnosis, including case conceptualization, that provides valuable information on how to approach therapy. In this was the PDM may be more valuable for University and College counselors. This is because the PDM, in addition to identifying symptoms, also provides a wholistic portrait of the person who has them. The usefulness of the holistic view of a person, that the PDM provides, is discussed and illustrated through a case study.